Do community-related traumatic events affect academic outcomes among adolescents? Quasi-experimental evidence from the Sewol disaster in South Korea. - Bethmann, Dirk; Cho, Jae Il (Death Studies, 2025)
The sinking of the South Korean ferry Sewol in April 2014 claimed a total of 304 lives. Among the victims were 250 students from Dan-won High School in the city of Ansan and 11 of their teachers. For the residents of Ansan, the tragedy marked the beginning of widespread psychological distress and overwhelming grief. Exploiting the disaster's quasi-experimental nature, we employ a difference-in-differences (DID) strategy to measure its impact on the academic performance of Ansan's high school students in 5 major subjects. Using peers from Ansan's neighboring cities as the control group, our results reveal that the disaster impaired performances particularly in mathematics and natural science, a finding that is more pronounced for female students. Our results highlight that it is of uttermost importance to provide comprehensive psychological support and interventions to traumatized students but also to the communities they live in to minimize adverse effects on educational attainment.